Observatorio de la vivienda urbana en Manizales, Caldas Arteaga Gustavo : parámetros de interés constructivos - Arteaga Botero, Gustavo Adolfo (Diseño, 2021)
The author addresses, in an original way and with a recognized methodological rigor, the study of the constructive conditions of urban housing that was promoted in the city of Manizales (central western Colombia) in a time frame of five years, making use of the so-called data mining. Overcoming the views that on the house put their focus of interest in purely typological aspects or execution of work, the author manages here to establish quantitative indicators that clearly relate the spatial attributes of the houses analyzed with their most representative technical characteristics: their constructive systems, the forms of the foundation, the interior divisions, the mezzany plates and the roofs, all this without neglecting the aspects of the urban and territorial context on which they are built. Thus, the housing observatory really becomes a good pretext that allows us to understand the complexity of the factors that affect its materialization. But beyond the exemplary treatment of the subject, the research makes a clear call on the importance of democratization in information and its management, which with an adequate translation and visualization must increasingly contribute to citizen participation in decision-making that concerns its built environment.